The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1021/acsami.1c20551
|View full text |Cite
|
Sign up to set email alerts
|

Highly Elastic and Corrosion-Resistive Metallic Glass Thin Films for Flexible Encapsulation

Abstract: Ternary CuZrTi metallic glass thin films synthesized by sputtering are suggested as highly flexible and corrosion-resistant encapsulation materials. Unlike nanocrystalline Cu and binary CuZr metallic glass thin films, the ternary CuZrTi metallic glass thin films retain amorphous structure and do not oxidize even after 1000 h in an accelerated harsh environment at 85 °C with 85% relative humidity. The encapsulation performance of 260 nm thick ternary CuZrTi metallic glass is maintained even after 1000 bending c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…In addition to the common‐used epoxy resins, novel acrylic monomers as adhesives also have promising applications in OSC encapsulation. [ 143 ] Recently, plasma polymers, [ 144 ] metallic glass, [ 145 ] and composite films [ 146 ] have also been used as encapsulation materials for OSCs. In general, inorganic encapsulation materials are effective in inhibiting the penetration of water and oxygen.…”
Section: Research Progress On Strategies To Enhance the Stability Of ...mentioning
confidence: 99%
“…In addition to the common‐used epoxy resins, novel acrylic monomers as adhesives also have promising applications in OSC encapsulation. [ 143 ] Recently, plasma polymers, [ 144 ] metallic glass, [ 145 ] and composite films [ 146 ] have also been used as encapsulation materials for OSCs. In general, inorganic encapsulation materials are effective in inhibiting the penetration of water and oxygen.…”
Section: Research Progress On Strategies To Enhance the Stability Of ...mentioning
confidence: 99%
“…Controlling the composition of the amorphous metal can improve the performance. Recently, our group reported that the ternary CuZrTi amorphous metal has excellent elastic deformation limit and structural stability compared to the binary CuZr amorphous metal. A laminate structure in which two materials are repeatedly stacked may highlight the advantages of each material. So, the two types of layers can interact complementarily in terms of mechanical and electrical properties. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant efforts have been made to improve the folding resistance of PI films, with a focus on enhancing the thermal stability and modulus of the material. However, these efforts have been largely limited to increasing intermolecular forces and have not involved actual folding resistance tests. Bea et al and Ahn et al have independently demonstrated the impressive folding resistance of PI/silica hybrids cross-linked with silane end-groups and PI films cross-linked through hydrogen bonds and coordination-based supramolecular networks, respectively. , These PI films have undergone 200000 folding/unfolding tests at a folding radius of 3 mm with promising results.…”
mentioning
confidence: 99%